Steel Moment-Resisting Frame Reliability via the Interval Analysis by FCM-PSO Approach considering Various Uncertainties - Jough, Fooad Karimi Ghaleh; Sensoy, Serhan (Taylor & Francis Ltd, 2020)
One important issue in compiling siesmic fragility curves is blending and incorporating uncertainties into the model under seismic conditions. Methods used in this regard are either approximate, costly and time-consuming. To address this, the optimized fuzzy method is used. To compile the fragility curve, epistemic and aleatory uncertainties have been incorporated in which model parameters are fuzzy values and FCM-PSO method is used to estimate mean and standard deviation of fragility curve. The FCM-PSO algorithm is trained using scenarios compiled via the IDA method. Results obtained from the full Monte Carlo method were used for verification. The method employed here is advantageous with regard to both accuracy and execution time.
Keywords: PSO Algorithm; Fuzzy Method; Collapse Fragility Curve; Epistemic Uncertainty; Interval Analysis